2000
DOI: 10.1080/174159700088027722
|View full text |Cite
|
Sign up to set email alerts
|

Model validation and verification of large and complex space structures

Abstract: In this paper two case studies of model validation and verification of large and complex space structures are presented. The first case study focuses on experience gained in performing model validat~on and verification of the mated Russian Mir Space Station and United States Space Shuttle. This study makes use of dynamic test data taken during the STS-81 flight associated with the Mir Structural Dynamics Experiment. The second case study involves the International Space Station P6 truss segment tested in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…For instance, most current vibration-based damage detection techniques observe changes in natural frequencies, modes of vibration, and frequency response functions (Loh and Tou, 1995;Doebling et al, 1996;Smyth et al, 2000;Farrar et al, 2001). Other techniques use subspace identification and updating (Abdalla et al, 1998;Pappa et al, 1998;Zimmerman, 2000;D'Souza and Epureanu, 2005a, b), wavelet analyses (Sohn and Farrar, 2001;Amizic et al, 2002;Amaravadi et al, 2002), and Ritz vectors (Cao and Zimmerman, 1999;Zimmerman, 1999). All these methods have been well developed for monitoring linear structures.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, most current vibration-based damage detection techniques observe changes in natural frequencies, modes of vibration, and frequency response functions (Loh and Tou, 1995;Doebling et al, 1996;Smyth et al, 2000;Farrar et al, 2001). Other techniques use subspace identification and updating (Abdalla et al, 1998;Pappa et al, 1998;Zimmerman, 2000;D'Souza and Epureanu, 2005a, b), wavelet analyses (Sohn and Farrar, 2001;Amizic et al, 2002;Amaravadi et al, 2002), and Ritz vectors (Cao and Zimmerman, 1999;Zimmerman, 1999). All these methods have been well developed for monitoring linear structures.…”
Section: Introductionmentioning
confidence: 97%
“…they are focused on determining changes in the frequencies and modes of vibration [14,24,36,49,60]. Other similar techniques use wavelet analyses [3][4][5]62], Ritz vectors [11,77], stochastic approaches [57,64], subspace updating [1,26,32,50,51,72,78,79], or evolutionary algorithms [80]. All these methods have been developed for monitoring linear structures.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods monitor changes in vibratory characteristics of a structure, which reflect damage. Several of these techniques use subspace identification and updating [3][4][5][6], wavelet analyses [7,8], and Ritz vectors [9,10]. Although there have been numerous studies showing that changes in observed linear features can be used to detect the presence of damage, the low sensitivity of these features (to damage) limits the applicability of such methods.…”
mentioning
confidence: 98%